Legendagem para Surdos e Ensurdecidos (LSE) de vídeos em libras - Souza, Eurijunior Sales de (2019)
The Subtitling for the deaf and hard-of-hearing (SDH), besides being a powerful inclusion tool, can be an excellent didactic resource for language learning. SDH also can be used in conjunction with other accessibility features, such as the Signer, but the initiatives that include their use in sign language videos are still rare. Among the genres of videos produced in Brazilian Sign Language, there is the genre translation of academic texts, commonly used in Language and Literature Programs with qualification in Brazilian Sign Language as a form of access of deaf students to these scientific texts in their mother tongue. This work, which has theoretical and methodological support in the studies of Accessible Audiovisual Translation (AVT), deals with the subtitling of this genre of videos. The methodology employed is the descriptive type. A video of the translation of a text that integrates the recommended bibliography of the Brazilian Sign Language and Literature program of the Federal University of Ceará was chosen. The research traces a descriptive analysis of this subtitling process, presenting the difficulties encountered, the peculiarities observed in this genre of videos and the strategies adopted by this researcher, with a view to the guidance of other subtitlers in task of become videos produced in Brazilian Sign Language accessible also to people who do not have fluency in that language